Posición sobre los componentes del sistema de evaluación, a propósito del área de lenguaje - Duarte A., Patricia; Ordoñez P., Carlos; Correa R., Miralba; Rincón B., Gloria; Pardo A., Neyla; Jurado V., Fabio; Bustamante Z., Guillermo; Hernández R., Daniel (Enunciación, 1996)